2022
DOI: 10.1007/s42452-022-04943-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of ginseng-derived exosome-like nanoparticles with sucrose cushioning followed by ultracentrifugation

Abstract: Ginseng is a traditional medicine that has been used for millennia. Asian ginseng (Panax ginseng Meyer) has multiple pharmacological properties. To determine the efficacy of ginseng-derived exosome-like nanoparticles (GDEs), GDEs should be isolated and characterized. GDEs from P. ginseng were isolated via sequential centrifugation using 68 and 27% of sucrose cushioning followed by ultracentrifugation. The size distribution, zeta potential, and morphology of GDEs were evaluated using DLS, NTA, and TEM. GDEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…A freeze-drying method for ginseng-derived nanoparticles was proposed, in which fresh particles were first stored in a deep freezer for 24 h and then transferred to a freeze-drying chamber under a vacuum for 96 h. Particles were obtained in powder form and exhibited no significant damage or loss in terms of morphology, RNA, or protein content after up to 60 days of storage at room temperature. These results suggested that freeze-drying is a potential option for facile vesicle storage after mass production [ 59 ].…”
Section: Characterization Of Pdvsmentioning
confidence: 99%
“…A freeze-drying method for ginseng-derived nanoparticles was proposed, in which fresh particles were first stored in a deep freezer for 24 h and then transferred to a freeze-drying chamber under a vacuum for 96 h. Particles were obtained in powder form and exhibited no significant damage or loss in terms of morphology, RNA, or protein content after up to 60 days of storage at room temperature. These results suggested that freeze-drying is a potential option for facile vesicle storage after mass production [ 59 ].…”
Section: Characterization Of Pdvsmentioning
confidence: 99%
“…They are also considered as a source of bioactive cargos, such as nucleic acids, proteins, growth factors, and lipids, and are indicative of the cell from which they are derived. , As such, EVs shed from cancerous cells are increasingly being studied as promising biological targets for therapeutics and detection of diseases . Numerous isolation techniques such as ultracentrifugation, size exclusion chromatography, immunoaffinity, precipitation, magnet, and antibody-based isolation methods have been studied by researchers for EV isolation . It is crucial that isolated EVs from biofluids preserve their functional activity for their use, for example, in disease diagnostics .…”
Section: Introductionmentioning
confidence: 99%
“…GDNs were isolated from ginseng using a modified centrifugation method and a sucrose gradient cushion system, as previously reported. 24 Ginseng was purchased from Geumsan (South Chungcheong, Korea) and sequentially washed with tap water, distilled water, and 1× phosphate-buffered saline (PBS). The material was then ground in a mixer for 2 min and subjected to serial low-velocity centrifugation to eliminate large impurities and debris (ESI Fig.…”
Section: Methodsmentioning
confidence: 99%